2002
DOI: 10.1046/j.1365-246x.2002.01794.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory depositional and compaction-caused inclination errors carried by haematite and their implications in identifying inclination error of natural remanence in red beds

Abstract: Summary Undetected depositional and/or compaction‐caused inclination errors may result in an overestimation of tectonically caused latitudinal offset. Hodych & Buchan used a single‐component isothermal remanent magnetization (IRM) acquired in a DC field at a 45° angle to the bedding to test for inclination errors in Silurian red beds. This approach was criticized by Stamatakos et al. We produced synthetic depositional and compaction‐caused inclination errors to test Hodych and Buchan's approach. Red bed sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 57 publications
1
20
1
Order By: Relevance
“…This extreme degree of shallowing is speculatively due to the combination of depositional inclination flattening, typical of the detrital haematite, and post‐depositional compaction of clays, which are particularly abundant in the carbonate‐depleted CMU. Tan et al (2002) found experimentally that during shallow (<100 m) burial compaction, clay‐size sediments containing detrital haematite particles can experience a magnetic inclination shallowing of 17°–19° starting from an induced inclination of 58°. For increasingly higher burial depths, which are usually associated with increasingly older sediments, compaction‐derived inclination flattening tends to increase accordingly (Tan et al 2002).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This extreme degree of shallowing is speculatively due to the combination of depositional inclination flattening, typical of the detrital haematite, and post‐depositional compaction of clays, which are particularly abundant in the carbonate‐depleted CMU. Tan et al (2002) found experimentally that during shallow (<100 m) burial compaction, clay‐size sediments containing detrital haematite particles can experience a magnetic inclination shallowing of 17°–19° starting from an induced inclination of 58°. For increasingly higher burial depths, which are usually associated with increasingly older sediments, compaction‐derived inclination flattening tends to increase accordingly (Tan et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Tan et al (2002) found experimentally that during shallow (<100 m) burial compaction, clay‐size sediments containing detrital haematite particles can experience a magnetic inclination shallowing of 17°–19° starting from an induced inclination of 58°. For increasingly higher burial depths, which are usually associated with increasingly older sediments, compaction‐derived inclination flattening tends to increase accordingly (Tan et al 2002). The difference in degree of flattening between the Forada CMU ( f = 0.35) and the Cicogna CMU ( f = 0.14) can be attributed to different compaction degrees of sediments with slightly different composition.…”
Section: Discussionmentioning
confidence: 98%
“…In this connection three different approaches have been recognized; (1) no inclination shallowing in coarse‐grained sediments but shallowing in clay‐sized sediments; (2) no inclination shallowing in fine‐grain sediments but shallowing in coarse‐grained sediments and (3) similar trend of inclination shallowing both in coarse and fine‐grained sediments. According to their experimental work, Tan et al . (2002) have claimed that hematite bearing clayey sediments underwent a compaction related inclination shallowing of 17°–19°, while coarse‐grained sediments received very little inclination shallowing.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all the compiled data sets have been extracted from the red beds, where the affects of secular variation have been sufficiently averaged out from the characteristic remanent magnetizations (which include depositional, post-depositional, and chemical magnetizations). Although, an anomalously shallow inclinations have been observed in some of the paleomagnetic directions, their respective declinations are considered as true image of the paleogeomagnetic field directions (Chauvin et al, 1996;Cogné et al, 1999;Bazhenov and Mikolaichuk, 2002;Tan et al, 2002;Narumoto et al, 2006;Tauxe et al, 2006). As shown in Fig.…”
Section: Compilation Of Paleomagnetic Datamentioning
confidence: 99%